ON IMPROVING THE INSTITUTION OF THE COMMISSIONER FOR HUMAN RIGHTS IN KAZAKHSTAN - Karzhaubaev, Серік Сейітұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The main task of Kazakhstan's domestic policy is the full protection of the rights and freedoms of citizens. Therefore, there are various state bodies in the country, one of the main tasks of which is to protect the rights of citizens. However, there is a lack of trust in these bodies in society. Among them, the Institution of the Commissioner for Human Rights stands out, the trust of society in which has not yet been lost. But the status and powers of the Commissioner for Human Rights require transformations. In order to improve the institution of the Commissioner for Human Rights in Kazakhstan, it is necessary to solve the following legal problems. The first is the strengthening of the legal status. Given the importance of the tasks of the Ombudsman, it is necessary to provide appropriate legal consolidation of his legal status in the Constitution of the Republic of Kazakhstan. In addition, the consolidation of his powers in a special constitutional law will raise the activities of the Ombudsman to a new level, contributes to the comprehensive protection of citizens' rights. The second problem is the mandatory implementation of the recommendations and appeals of the Authorized state bodies. The lack of responsibility of officials for non-compliance with the recommendations and appeals of the Commissioner for Human Rights is one of the reasons for the inefficiency of the work of the Ombudsman institution. The article substantiates the need to introduce disciplinary and administrative responsibility of officials for non-compliance with the recommendations and appeals of the Commissioner for Human Rights. The third problem is the empowerment of the Commissioner for Human Rights with the right to appeal to subjects who have the right of legislative initiative with proposals for improving the current legislation. In its law enforcement practice, the Commissioner for Human Rights identifies problems of the current legislation that require solutions. Therefore, this right contributes to the improvement of legislation. The fourth problem is the mandatory interaction of the Commissioner for Human Rights with the media. The importance of such interaction is one of the necessary and effective means to implement the powers of the Ombudsman.